Fiqh Prioritas sebagai Instrumen IjtihÃ¢d MaqÃ¢á¹£idÃ® Perspektif YÃ»suf al-QarÃ¢á¸awÃ® dan Urgensinya di Era Kontemporer - Jauhari, Nashrun (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2016)
The article attempts to analyze Fiqh of Priority as an instrument of ijtihÃ¢d maqÃ¢á¹£idÃ® from YÃ»suf al-QarÃ¢á¸awÃ®âs perspective and its significance within the contemporary era. The position of the Fiqh of Priority within the study of Islamic law is a part of the conceptual developments of ijtihÃ¢d which is based on maqÃ¢á¹£id al-sharÃ®âah and has been oriented into Fiqh of DaÊ»wah. The Fiqh of Priority along with its principles can be functioned as a reference in stipulation of the Islamic law (ijtihÃ¢d al-ah}kÃ¢m). This is because the Fiqh of Priority is built on the priority values revealed in al-QurâÃ¢n and mentioned in H{adÃ®th as well as based on the concept of tadarruj al-ah}kÃ¢m (gradation of stipulation of the Islamic law) during the Prophet Muhammadâs lifetime. Epistemo-logical framework of the Fiqh of Priority consists of three main principles, i.e. the principles of gradation in the Islamic law (al-fiqh bi marÃ¢tib al-aâmÃ¢l), the principles of attitude towards the reality of law (fiqh al-wÃ¢qiâ li al-ah}kÃ¢m), and the principles of dealing with contradiction between arguments or reasoning between the stipulation of law and social reality